Assessing Destination Brand Image Chinatown In Term of Semarang City Branding Implementation - Ristianti, Novia Sari; Dewi, Santy Paulla (Universitas Negeri Semarang, 2018)
Abstract. Concerning to city branding, the role of brand image is very important for visitors to remember the tourism destination. The destination brand image can identify by 5 elements of city image, namely path, edge, node, district, and landmark. Semarang Chinatown is one of the historical tourism sites in Semarang that can represent the Semarang's city branding as a